The concept of the word “Culture” in Iranian ancient texts - Tahami, Morteza (2021)
This study analyzes the concept of the word “culture” in Iranian ancient texts. The implementation is done using the bibliographical resources available to the authors. The research findings are collected from ancient texts, especially the Middle Persian texts. Research methodology has a narrative-citation nature. To understand any phenomenon, it is necessary to understand the historical process of that phenomenon. Since culture is an essential element in the evolution of a society, an examination of its historical process helps to understand the meaning and meaning of the term in the main texts and in Iranian life. Hence, because of the importance of culture, here we have explored the meanings and concepts of culture from the perspective of ancient texts. Results show that the culture the word is made up of two components: frā meaning (“forward and up”); and hong, from the root of sang, meaning “pull” or “drag and carry”. As a result of education, human beings acquire knowledge and acquire skills, and these acquired knowledge and skills are also called culture. In addition, in ancient Iranian texts, culture has come to mean politeness.